Online Business Games in the Insurance Industries â?? An Attempt to Prepare Attendees for their Later Working Life as Self-employed Workers (doi: 10.3991/ijac.v1i2.605) - Blum, Patrick (International Journal of Advanced Corporate Learning (iJAC), 2008)
In Europe, the basic education for sales personnel in the insurance industries is regulated by law to guarantee a secure customer oriented sales process. This education mainly targets insurance-knowledge, -law, -conditions and the sales process. It does not prepare the attendees for their working life as a self-employed worker. To overcome this problem online business games are used because of their abilities to master complexity, to achieve higher cognitive objectives, to learn from mistakes without risk through trial and error, and to learn from operating experience through time-lapse. On the basis of the online business game â??SiVA